Adoption of the shariah-compliant e-wallet among young muslims in Kedah - Muhammad Asyraf, Ibrahim@Ishak (2023)
E-wallet was an innovative payment instrument that arose under financial technology. E-wallet helps ease the user’s daily life, in which users can make daily transactions without using notes or coins. Indirectly, E-wallet also helps to reduce the risk of cash being stolen. Undeniably, an E-wallet brings more benefits than disadvantages. The primary aim of this study is to examine the factors affecting the adoption of Shariah-compliant e-wallets among young Muslims in Kedah. The questionnaire consisted of 29 questions, was distributed to the respondents, and successfully collected 236 feedbacks. Firstly, this study applied factor analysis to construct all the variables. Also, Cronbach’s α coefficient was computed to determine internal consistency reliabilities. Then, this study used regression analysis to test the relationship between the variables. The regression analysis showed that users would adopt a Shariah-compliant e-wallet when they perceived it as easy to use and useful. In contrast, shariah compliance is insignificantly in adopting Shariah-compliant e-wallets. These results help the E-wallet service providers identify the significant factors influencing users to use E-wallet services. Lastly, this study recommended that e-wallet provider companies raise awareness and promote products that comply with Shariah principles. It is because a large number of users are still unable to differentiate between e-wallets that are permissible according to Shariah guidelines.